PENGARUH REKRUTMEN TERHADAP KINERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT (BPR) PRISMA DANA MANADO - Kamila Puliki; Daisy Sundah; Lietje Lumatauw (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
The recruitment process is one of the most important things in the activities of an organization/company. Therefore an organization/company that moves and earns profit because it is supported by the existence of human resources in the organization/company. In this way, the performance of employees in the company will be considered satisfactory because the recruitment process is considered appropriate. Therefore the authors want to know the recruitment process, employee performance and whether the influence of recruitment on employee performance at PT. Bank Perkreditan Rakyat Prisma Dana Manado. The purpose of this study is to determine the recruitment process, to determine employee performance and to determine the effect of recruitment on employee performance at PT.Bank Perkreditan Rakyat Prisma Dana Manado. This type of research is quantitative with descriptive research methods. This study took samples from the population, namely all employees who work at PT. Bank Perkreditan Rakyat Prisma Dana Manado with a total population of 59 people. The author uses a questionnaire as a data collection tool. The recruitment process carried out by PT. Bank Perkreditan Rakyat Prisma Dana Manado, namely Applicants who complete forms, take written tests, take psychological tests, attend material debriefing and sign cooperation contracts through third parties. Employee performance at PT. Bank Perkreditan Rakyat Prisma Dana Manado seen from the calculation of the total score of 1,738 with a percentage level of 84% with a categorization close to very good. From the results of the study, it was found that recruitment according to employee performance.